Targeting Wnt Signaling in Cancer: Opportunities Abound If We Can Avoid the Sword of Damocles - Kahn, Michael; Lai, Keane (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dysregulation of Wnt signaling is known to be associated with various cancers. As such, identification of novel Wnt pathway targets in cancer and better characterization of already-known targets present exciting, emerging opportunities for cancer treatment. In this Special Issue, we feature papers which discuss the role of Wnt signaling and associated targets in cancer metabolism, tumor immune response, and tumor microenvironment. Papers discussing a range of Wnt-mediated cancers, including those of the colon, liver, pancreas, synovium, bladder, etc., are included.